Stem Cell-Based Therapy for Diabetic Foot Ulcers - Yu, Qian; Qiao, Guo-hong; Wang, Min; Yu, Li; Sun, Yaoxiang; Shi, Hui; Ma, Tie-liang (Frontiers in Cell and Developmental Biology, 2022)
Diabetic foot ulcer (DFU) has become a worldwide clinical medical challenge as traditional treatments are not effective enough to reduce the amputation rate. Therefore, it is of great social significance to deeply study the pathogenesis and biological characteristics of the diabetic foot, explore new treatment strategies and promote their application. Stem cell-based therapy holds tremendous promise in the field of regenerative medicine, and its mechanisms include promoting angiogenesis, ameliorating neuroischemia and inflammation, and promoting collagen deposition. Studying the specific molecular mechanisms of stem cell therapy for diabetic foot has an important role and practical clinical significance in maximizing the repair properties of stem cells. In addition, effective application modalities are also crucial in order to improve the survival and viability of stem cells at the wound site. In this paper, we reviewed the specific molecular mechanisms of stem cell therapy for diabetic foot and the extended applications of stem cells in recent years, with the aim of contributing to the development of stem cell-based therapy in the repair of diabetic foot ulcers.